Analisis Implementasi Intensifikasi Pemungutan Pajak Hotel Atas Rumah Kos Di Badan Pelayanan Pajak Daerah Kabupaten Bekasi - Zahran, Wahidin Septa; Irwansyah, Iwan; Isfianita, Isfianita (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Tax is the major revenue source for Indonesia. The tax collecation in Indonesia most frequently is not reached the target even there is lower pattern since 2019. Intensification actions of hotel tax at the boarding house is not optimally yet in Bekasi District so on be an interesting to be analyzed. This research is aim to analyze the implementation of intensification actions on hotel tax at boarding houses by Badan Pelayanan Pajak Daerah Bekasi District. The result of this study indicate that communication is well implemented by the support of software saving box and jumped into field directly, however it is not optimally yet related information distribution consistently, included sanction potential. The resoruces related facilities and infrastructure is not good enough in order to support tax collection in staff numbers. The disposition of employee is enough good and offers convenience for taxpayers to pay the taxes, however it is not optimally yet in employee’s dedication. Bureaucracy structure is categorized as good, however there is problem following the lower education level of Taxpayers that bring influence towards fiscus’s performance.